2013
DOI: 10.1021/bc4001917
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Quantum Dots Used for In Vitro Cellular Labeling: Role of QD Surface Ligand, Delivery Modality, Cell Type, and Direct Comparison to Organic Fluorophores

Abstract: Interest in taking advantage of the unique spectral properties of semiconductor quantum dots (QDs) has driven their widespread use in biological applications such as in vitro cellular labeling/imaging and sensing. Despite their demonstrated utility, concerns over the potential toxic effects of QD core materials on cellular proliferation and homeostasis have persisted, leaving in question the suitability of QDs as alternatives for more traditional fluorescent materials (e.g., organic dyes, fluorescent proteins)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 100 publications
(188 reference statements)
8
108
0
1
Order By: Relevance
“…In reality, toxicity is a complex issue with a notable disconnect between studies with cell models and those with animal models: cytotoxicity associated with QDs does not directly translate into toxicity in animal models [10 ,11 ]. Although it is prudent to remain cautious about the prospect of in vivo administration of QDs to humans, the potential toxicity of QDs is not a compelling argument against their use as cellular or in vivo probes for fundamental studies on model systems, but rather a directive to use high-quality and well-characterized materials, which many studies have shown to be non-cytotoxic at doses and exposures relevant to experiments (for recent examples, see [12,13]). Moreover, it is impractical to argue that QDs should be avoided for in vitro assays because of their 'toxic' cadmium content -the amount of QDs in a typical assay ( 10 À11 mol QD per sample, or 100 mg Cd) is no more cadmium than the average North American or European adult consumes as part of their weekly diet ($175 mg) [14].…”
Section: Bright Emittersmentioning
confidence: 99%
“…In reality, toxicity is a complex issue with a notable disconnect between studies with cell models and those with animal models: cytotoxicity associated with QDs does not directly translate into toxicity in animal models [10 ,11 ]. Although it is prudent to remain cautious about the prospect of in vivo administration of QDs to humans, the potential toxicity of QDs is not a compelling argument against their use as cellular or in vivo probes for fundamental studies on model systems, but rather a directive to use high-quality and well-characterized materials, which many studies have shown to be non-cytotoxic at doses and exposures relevant to experiments (for recent examples, see [12,13]). Moreover, it is impractical to argue that QDs should be avoided for in vitro assays because of their 'toxic' cadmium content -the amount of QDs in a typical assay ( 10 À11 mol QD per sample, or 100 mg Cd) is no more cadmium than the average North American or European adult consumes as part of their weekly diet ($175 mg) [14].…”
Section: Bright Emittersmentioning
confidence: 99%
“…Review papers summarizing the studies performed on the toxicity of different photoluminescent nanoparticles have been reported, including gold nanoparticles [193][194][195][196], QDs [197][198][199][200][201], lanthanide-based nanoparticles [179,[202][203][204], and C-dots [205]. However, individual toxicity evaluations need to be completed for each developed nanoplatform to completely assure its safety for biomedical applications.…”
Section: Toxicitymentioning
confidence: 99%
“…They have the ability to elucidate the pharmacokinetics and pharmacodynamics of drug applicant and serve as a "traceable" drug delivery system. [1][2][3][4][5] In 1984, the Russian physicist Ekimov first discovered QDs in glass crystals. After 1984, a systemic advancement in pharmaceutical sciences was driven, and a relationship was established between the size and band gap for semiconductor nano particles (by applying a particle in a sphere model) approximation to the wave function for bulk semiconductors.…”
Section: Introductionmentioning
confidence: 99%